THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CUSTOMER LOYALTY AT MANNERS COFFEE AND SOCIETY - Sulaeman, Kurniawan Saputra; Musa, Chalid Imran; Haeruddin, Muhammad Ilham Wardhana (Universitas Negeri Makassar, 2026)
Abstract: This study aims to examine the effect of product quality and price on customer loyalty at Manners Coffee and Society. This research uses a quantitative approach with an explanatory nature. The population and sample in this study consisted of 50 loyal customers of Manners Coffee and Society. Data collection was conducted using questionnaires, and data analysis was performed using simple linear regression analysis with the assistance of Statistical Product and Service Solutions (SPSS). The results of the analysis show that, partially, product quality and price have a significant effect on customer loyalty at Manners Coffee and Society. Simultaneously, product quality and price also have a significant effect on customer loyalty at Manners Coffee and Society.Keywords: Effect of Product Quality, Price, and Customer Loyalty.